Peran Manajemen Sumber Daya Manusia dalam Pengembangan Bisnis Kecil dan Menengah (UKM) - Anggraini, Septi; Lifoniar, Afrima; Anggraini, Vatika (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
An increase in per capita income is the goal of national economic development, success in national development because of the existence of economic growth indicators. Micro, Small and Medium Enterprises (MSMEs) for jobs and encourage economic growth because they absorb a lot of labor so that MSMEs can reduce the unemployment rate. Human resource management (HRDM) is the management of labor or employees both in the organization and in the company. Labor is indeed needed by companies so that in obtaining labor requires recruitment, selection, assessment and compensation. The qualitative research method is descriptive and uses secondary data from the BPS website. Small and Medium Enterprises (SMEs) play an important role in the economies of many countries, including Indonesia. In the development process, various factors are very influential, one of which is the management of human resources (HR). Effective HR management can be a key driver to improve the productivity, product quality, and competitiveness of SMEs in the global market. This article aims to explore how the role of HR management in supporting the development and sustainability of SMEs. This study examines various aspects of HR management, ranging from recruitment, training, development, to performance management, which can have a positive impact on SMEs.